2015
DOI: 10.2147/ccid.s86418
|View full text |Cite
|
Sign up to set email alerts
|

Associations between cardiovascular risk factors and psoriasis in Iran

Abstract: BackgroundPsoriasis is a common chronic inflammatory skin disease. There is overwhelming evidence on the higher risk of cardiovascular diseases in patients with psoriasis as a result of hyperlipidemia, which is more common in these patients.ObjectivesThe aim of this study was to elucidate the association between the cardiovascular risk factors and psoriasis.MethodsIn a cross-sectional study, 55 patients with psoriasis and 55 matched (sex and age) controls were entered the study at the Department of Dermatology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…In addition, the study indicated that dyslipidemia was more common among patients with psoriasis compared to controls, which was consistent with findings of studies conducted by Fernandez-Armenteros et al, 18 Goolam Mahyoodeen et al, 12 and Gui et al 1 Furthermore, we found higher prevalence of hypertension among patients with psoriasis relative to controls, which was in agreement with studies conducted in Iran, 13 India, 9 South Africa, 12 and Poland, 10 while it was inconsistent with studies conducted in China 1 and Korea. 19,28 These discrepancies might be due to racial and cultural differences.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In addition, the study indicated that dyslipidemia was more common among patients with psoriasis compared to controls, which was consistent with findings of studies conducted by Fernandez-Armenteros et al, 18 Goolam Mahyoodeen et al, 12 and Gui et al 1 Furthermore, we found higher prevalence of hypertension among patients with psoriasis relative to controls, which was in agreement with studies conducted in Iran, 13 India, 9 South Africa, 12 and Poland, 10 while it was inconsistent with studies conducted in China 1 and Korea. 19,28 These discrepancies might be due to racial and cultural differences.…”
Section: Discussionsupporting
confidence: 92%
“…8 Farshchian et al found that the mean of triglyceride, total cholesterol, blood pressure, and body mass index (BMI) were higher among Iranian patients with psoriasis compared to controls. 13 Gui et al found a higher prevalence of metabolic syndrome among patients with psoriasis compared to controls in a Chinese population (14.3% vs 10.%, p=0.001) with OR of 1.5. 1 However, the mechanism of this association is not fully understood.…”
Section: Introductionmentioning
confidence: 96%
“…Among these components, we could not establish any existing relationship of lowered HDL-C as a risk factor in psoriasis patients. Despite several studies suggesting impaired serum levels of lipids and lipoproteins as an important risk factor for CVD among psoriasis patients, many of the reports remain controversial (Farshchian et al 2007;Toker et al 2009;Ma et al 2014). However, our result was found to be in agreement with Cohen et al (2010), who reported 48.6% dyslipidaemia in psoriasis patients in comparison to 37.9% Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Two review authors [SC] and [RP] extracted the data which were crosschecked by the third author [DP]. Extracted data included author's names, year of publication, region, means and SD level of age, TGY (Uyanik et al 2002;Piskin et al 2003;Farshchian et al 2007Farshchian et al , 2015Akhyani et al 2007;Dreiher et al 2008;Balci et al 2010;Choi et al 2010;Langan et al 2012;Vayá et al 2013;Pehlevan et al 2014;Akcali et al 2014;Taheri Sarvtin et al 2014;Parodi et al 2014;Irimie et al 2015;Barrea et al 2016;Ražnatović-Đurović et al 2016;Coban et al 2016;Praveenkumar et al 2016;Uczniak et al 2016;Sharma et al 2016;Kothiwala et al 2016;Singh et al 2017;Girisha and Thomas 2017;Milčić et al 2017;Ganguly et al 2018), HDL-C (Piskin et al 2003;Farshchian et al 2007Farshchian et al , 2015Akhyani et al 2007;Dreiher et al 2008;Balci et al 2010;Choi et al 2010;Langan et al 2012;Vayá et al 2013;Pehlevan et al 2014;Akcali et al 2014;…”
Section: Data Extraction and Study Quality Assessmentmentioning
confidence: 99%
See 1 more Smart Citation